Integrated Nitrogen Management in Maize-Wheat Cropping Sequence on Typic Haplustalfs of Western India - Totawat, K L; Somani, L L; Singh, R; Singh, G (Annals of Arid Zone, 2016)
A field investigation involving three sources (chemical, organic and chemical + organic) and three levels of nitrogen .(50, 75 and 100% of the recommended dose). in conjunction with two levels of bio-inoculant (no-inoculation and in’oculation with Azotobacter) was carried out on a Typic Haplustalfs of Udaipur (Rajasthan), India. using maize and wheat crops in cropping sequence. Application of N at 100% of the recommended dose through organic manure alone or in integra ion with inorganic fertilizer on equal N basis as compared to when applied solely through chemical fertilizer enhanced the growth, yield attributes and yields of both the crops along with uptake of nutrient and protein content. Inoculation withAZOlObacter also improved these parameters under study. Improvements in available nutrient status of the soil under these treatments suggest the rational way to sustain the crop production.